Radioactive Iodine Remnant Ablation: The Beta-knife Completion Thyroidectomy - Gulec, Seza (Mol Imaging Radionucl Ther, 2017)
The rationale and objectives for radioactive iodine (RAI) ablation remain perplexing to many. This review addresses the meaning, clinical context and the goals of “ablation”: the RAI treatment after a total thyroidectomy. This article also aims to clarify the definition of a total thyroidectomy and how a thyroid remnant can introduce a confounding factor in the postoperative management of patients with differentiated thyroid cancer. The implications of an existing thyroid remnant on RAI diagnostic imaging and serum thyroglobulin levels are discussed. This review provides a rational approach validating the utility of RAI remnant ablation regardless of the patient’s risk stratification.